1999
DOI: 10.1099/00221287-145-9-2453
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of tonB in Bordetella bronchiseptica and Bordetella pertussis prevents utilization of ferric siderophores, haemin and haemoglobin as iron sources The GenBank accession number for the sequence reported in this paper is AF087669.

Abstract: The Bordetella bronchiseptica tonB gene was cloned by detection of a chromosomal restriction fragment hybridizing with each of two degenerate oligonucleotides that corresponded to Pro-Glu and Pro-Lys repeats characteristic of known TonB proteins. The tonB Bb gene was situated upstream of exbB and exbD homologues and downstream of a putative Fur-regulated promoter. Hybridization results indicated that the tonB operon and flanking regions were highly conserved between B. bronchiseptica, Bordetella pertussis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
0
27
0
1
Order By: Relevance
“…The growth yield of the tonB strain was decreased in iron-restricted medium lacking norepinephrine compared to those of the wild-type and complemented mutant strains. This result likely reflects the contribution of alcaligin-mediated acquisition of transferrin-iron to the growth of B. bronchiseptica, since ferric alcaligin transport is TonB dependent (39). Mutational analysis of putative TonB-dependent receptor genes.…”
Section: Resultsmentioning
confidence: 99%
“…The growth yield of the tonB strain was decreased in iron-restricted medium lacking norepinephrine compared to those of the wild-type and complemented mutant strains. This result likely reflects the contribution of alcaligin-mediated acquisition of transferrin-iron to the growth of B. bronchiseptica, since ferric alcaligin transport is TonB dependent (39). Mutational analysis of putative TonB-dependent receptor genes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that the siderophoremediated iron binding may function upstream of and provide free iron to the oxidase-permease iron uptake system. It has been reported that disruption of tonB in Bordetella bronchiseptica and Bordetella pertussis prevents utilization of ferric siderophores, hemin, and hemoglobin as iron sources (30). Thus, it is possible that the siderophore uptake mechanism is related to the use of hemoglobin iron by C. albicans.…”
mentioning
confidence: 99%
“…In response to iron starvation, they produce the macrocyclic dihydroxamate siderophore alcaligin (15,53) and also use a variety of heterologous siderophores, including enterobactin (7), ferrichrome, and desferrioxamine B (6), for iron retrieval. These organisms can also obtain iron from host sources transferrin (60,61), lactoferrin (61), heme (1,55), and hemoglobin (55).…”
mentioning
confidence: 99%